2020
DOI: 10.1177/2151459320911844
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Iron May Improve Outcomes in Elderly Patients With Operative Hip Fractures

Abstract: Introduction: Hip fractures are common injuries with high morbidity and mortality rates. These patients often become anemic and require allogenic blood transfusion. Transfusions are costly with potential complications. This study examines the effect of intravenous (IV) iron on patients with hip fractures, undergoing surgery within 48 hours, and being treated with a highly restrictive transfusion protocol. Materials and Methods: A retrospective chart review performed on patients admitted to a level 1 tertiary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…After study selection, according to our predefined protocol, 36 fulltext manuscripts were reviewed and from these 13 studies, 3718 patients were suitable for inclusion in the review. [23][24][25][26][27][28][29][30][31][32][33][34][35] (Figure 1) The studies excluded after full-text review are presented in Supporting Information S1. Of the included studies, four were randomized trials (732 patients) 23,25,28,32 and nine were nonrandomized studies (2986 patients).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After study selection, according to our predefined protocol, 36 fulltext manuscripts were reviewed and from these 13 studies, 3718 patients were suitable for inclusion in the review. [23][24][25][26][27][28][29][30][31][32][33][34][35] (Figure 1) The studies excluded after full-text review are presented in Supporting Information S1. Of the included studies, four were randomized trials (732 patients) 23,25,28,32 and nine were nonrandomized studies (2986 patients).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies, two RCTs 25 , 35 (456 participants) and one nonrandomized study 32 (1634 participants) reported discharge hemoglobin. While a difference was demonstrated in discharge hemoglobin in the nonrandomized study, there was no difference in discharge hemoglobin between groups in the RCT (Supporting Information: Figure S6 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies found that up to 70% of the these patients need perioperative allogeneic blood transfusion [14,26]. It is described that the major factors that have an in uence to receive blood transfusion are age, comorbidities, type of fracture and surgery performed (extracapsular fractures treated with intramedullary nailing are the cause of more anaemia) [26], the type of surgery performed and the haemoglobin concentration at admission [7,14]. Close monitoring of patients and presurgical optimization have made that in our sample the level of blood transfusions have increased from 27.2% in 2012 to 53.1% in 2017.…”
Section: Discussionmentioning
confidence: 99%
“…A Spanish randomized controlled trial conducted in 2005, showed that in certain subgroups peri-operative iron infusions decrease the requirements for later RBC transfusion and reduce rates of nosocomial infections [18]. A recent US study has shown that the use of IV iron decreases length of hospital stay and readmission rates in hip fracture patients [19]. However, there is a need for further research in this area.…”
Section: Introductionmentioning
confidence: 99%